Potentials and role of peripheral or weakly structured regions in national innovation systems - Henning Kroll; Knut Koschatzky (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2020)
It is the objective of this paper to analyse the role innovation policy could play in the promotion of regional change, using Germany as a case study, and to develop a typology of structurally weak regions for tailored and regionally specific policy interventions.
urn:nbn:de:0011-n-5821877
Keywords: 330